The Effect of Time Management and Learning Motivation on Academic Procrastination - Jalaluddin 'Irfan Fuadi; Fauzan Almanshur (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to explore the impact of time management and learning motivation on academic procrastination among students of the Management Study Program, Faculty of Economics, UIN Maulana Malik Ibrahim Malang. This research utilizes a quantitative method with a survey approach involving 285 students as a sample selected using proportional random sampling. Data were collected through a Google Form questionnaire and analyzed using the Structural Equation Modelling-Partial Least Square (SEM-PLS) method with SmartPLS 3.0 software. The results show that both time management and learning motivation significantly affect academic procrastination, both partially and simultaneously. Good time management and high learning motivation have been proven to reduce academic procrastination levels. Therefore, to reduce academic procrastination, students need to develop effective time management skills and increase their learning motivation.